LULC Map Comparison: Comparison and validation of land use land cover maps derived from satellite imagery - Silva, Fábio Miguel Domingues da (2022)
Dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Science in Geospatial Technologies